Factors that impact consumer adoption of mobile banking within the m-commerce domain - Matthew, Darrel (My University, 2014)
Cannot copy abstract.
Thesis (M.M. (ICT Policy and Regulation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2013.
Keywords: Cell phone banking; Mobile banking; South Africa; Consumer motivation